CompTIA Network+ N10-007 Exam Cram - Dulaney, Emmett A. (Pearson IT Certification, 2018)
The CompTIA Network+ N10-007 Exam Cram, Sixth Edition has been updated to prepare candidates for the new exam, using the proven Exam Cram method of study. The CompTIA Network+ N10-007 Exam Cram, Sixth Edition is the perfect study guide to help you pass the CompTIA Network+ N10-007 exam. It provides coverage and practice questions for every exam topic, including substantial new coverage of security, cloud networking, IPv6, and wireless technologies. The book presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Exam Alerts, sidebars, and Notes interspersed throughout the text keep you focused on what you need to know. Cram Quizzes help you assess your knowledge, and the Cram Sheet tear card is the perfect last-minute review. As with all Exam Cram books, it includes: Chapters that map directly to the exam objectives Comprehensive foundational learning on all topics covered on the exam An extensive collection of practice questions Access to the Pearson Test Prep practice test software that provides real-time practice and feedback, online or offline The Cram Sheet tear-out card including tips, acronyms, and memory joggers not available anywhere else - perfect for last-minute study